THE INFORMATION CONTENT OF MANAGEMENT EARNINGS FORECASTS: AN ANALYSIS OF HARD VERSUS SOFT INFORMATION. (17th June 2013) - Brockman, Paul; Cicon, Jim
Abstract: We examine the announcement effects of hard (quantitative) and soft (qualitative) information contained in management earnings forecasts. Consistent with previous studies, we confirm a positive relation between the earnings surprise component of the announcement and the magnitude of the abnormal return. In contrast to previous studies, we examine the effect of soft information on abnormal returns while controlling for hard information. Our results show that soft information generally explains more of the announcement effect of earnings forecasts than does hard information. Overall, our findings contribute to the growing literature that examines the economic significance of qualitative information.